(3LQjeI GdJMQjV GdYdfi (B/ s - (3YHOGddWja CMeO YHOGdYXje GdTjNs; (3YeQ eMeO eMeO SGde (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI ,s, 2017)
(3oYpQa GdJMQjV efP GdbOe MjfeG MQV EHdjS CHG GdHTQjI hRhLg (B"(3BOe hMhGA(B" -(3YdjgeG GdSdGe(B- (3HCf jCcdG ef GdTLQI eNGdkaG CeQ Gddg HGdfgj Yf GdCcd efgG(B: (3hoYQa GdJMQjV aj GddZI HCfg(B: (3GdJNUjU hGdJMQjV Ydi GdbJGd hGdMK hGdEMeGA Ydjg(B. (3hGNJda Gdabg Ydi aQjbjf(B: (3efge ef jLYd GdbUO GdLfGFj hGdCgdjI GdLfGFjI YfUQ hjhUa GdeMQV Ydi ef jOaY HTNU Pi CgdjI LfGFjI SjF GdfjI Edi GQJcGH LQjeI hjTJQW GdCgdjI hShA GdfjI(B. (3haQjb BNQ jYQa GdJMQjV Ydi cd ef MnqQV BNQ hdG jTJQW GdCgdjI hShA GdfjI(B. (3hGdTQjYI GdESdGejI JfGhdJ GdJMQjV(B: (3hgfG jchf GdJMQjV EeG Edi aYd MSf Ch Edi LQjeI(B: (3hfLO GdJTQjYGJ GdhVYjI(B: (3GdHYV efgG JfGhd GdJMQjV Ydi Efg eSGgeI aj GdLQjeI hfU Ydi LQGFe eYjfI JeS GdOhdI hCfgG LQjeI JMQjV eSJbdI s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2017s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJMQjVs; (3GdLQjeI s; (3GdbGfhf GdLfGFis; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3cdjI GdMbhbs